China's Technology Innovators Selected Cases on Creating and Staying Ahead of Business Trends - Zhu, Xiaoming (Management for Professionals,, 2018)
This book is one of the first to explore how Chinese companies are feeling the impulse of emerging business trends and seizing opportunities brought by technology innovation. It consists case studies of 7 Chinese companies: 3DMed, Wechat from Tencent, Shanghai GM, CP Group, Alibaba, AutoNavi, and ICBC. Each Chinese company has its unique perspectives and different ways to make transformation and business model adjustments. The book helps fill the gap between the global interest in "Innovate in China" and the limited availability of cases on innovations in the country. It is a valuable reference resource for readers in China and beyond wishing to address challenges in the context of growing digital technologies and overwhelming business trends.